2012
DOI: 10.1097/igc.0b013e31826fd66b
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Management of Early Cervical Cancer Among Members of the GCIG

Abstract: There are wide variations in the use of preoperative imaging, when pelvic and para-aortic lymph nodes are removed, and as to which surgical procedure should be offered in the management of cervical cancer both when fertility conservation is and is not an issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…To what extent national guidelines are applied in the therapy for cervical cancer can only be determined on the basis of characteristic reimbursement data or with the help of questionnaires [47,48]. Whereas the former is only meaningful when a separate character can be coded for every possible treatment modality, the latter is dependent on a high participation.…”
mentioning
confidence: 99%
“…To what extent national guidelines are applied in the therapy for cervical cancer can only be determined on the basis of characteristic reimbursement data or with the help of questionnaires [47,48]. Whereas the former is only meaningful when a separate character can be coded for every possible treatment modality, the latter is dependent on a high participation.…”
mentioning
confidence: 99%
“…The most challenging group of tumours is FIGO stage IB1 tumours. For tumours smaller than 2 cm and stromal invasion of less than 10 mm (or half of the stroma), VRT or ART are usually indicated [ 21 ]. IB1 tumours larger than 2 cm and IB2 tumours that have a 30–40% risk of lymph node involvement are considered impropriate for fertility-sparing procedures or with a low chance of achieving a fertility preservation [ 22 ].…”
Section: Preoperative Workoutmentioning
confidence: 99%
“…A recent survey conducted among Gynaecologic Cancer Intergroup (GCIG) members revealed that some of the fertility preservation procedures were offered by all centres, while 20.3% offered ART, 47.3% VRT and 58.1% ST [ 21 ]. The differences in indications were based mainly on local preferences and experiences rather than based on certain criteria.…”
Section: Trachelectomy Surgical Techniquesmentioning
confidence: 99%
“…There is growing appreciation within the gynecological oncology community of the potential to reduce morbidity and retain fertility without compromising oncological outcomes through the adoption of less radical surgical approaches. 1 For those patients requesting fertility conservation, there is emerging evidence suggesting less radical procedures (Large Loop Excision of Transformation Zone (LLETZ), conization or simple trachelectomy, incorporating bilateral pelvic lymph node dissection [BPLND]) are associated with comparable oncological outcomes to RT with less morbidity. 2Y9 Therefore our center, in common with others worldwide, has moved toward less radical treatment in selected cases of early cervical cancer who wish fertility conservation.…”
mentioning
confidence: 99%